Why power matters in Payments for Environmental Services (PES) - Jean Carlo Rodríguez de Francisco; Rutgerd Boelens (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
Payments for environmental services (PES) are payments to land owners whose land management practices help to provide environmental services (ES). In the context of watershed environmental services, the most important services are the supply, purification and regulation of water. PES was conceived as an instrument for facilitating the transition to a green economy. From this perspective, PES is a win-win solution to environmental degradation and poverty. Today, PES is a widely used policy tool for conservation. Having begun life as scattered, privately funded projects, PES has made its way into many national and internation¬al conservation policies around the world. The value of PES watershed transactions in 2011 was USD 8-10 billion; and the figure is still growing fast. This briefing paper challenges the notion of PES as a panacea for environmental degradation and poverty. While PES is a rapidly proliferating mechanism for natural resource management and conservation, its use is sometimes coupled with a lack of understanding of its social and econo¬mic impacts. To this end, we identify a number of critical issues that have received marginal policy attention in the context of the developing world, but which have a great deal of social relevance and impact. Understanding the critical issues surrounding PES can help to overcome and reduce the following drawbacks: Power asymmetries in PES negotiations. PES often involves governments and private enterprises negotiating with marginalised communities. These actors' differing resources and capabilities are likely to influence both the outcomes of negotiations and the operation of PES. Ensuring that the interests of marginalised communities are protected in PES negotiations is not just a social imperative, but also contributes to sustainability. PES participation is not always voluntary. Environ¬mental laws, strict contract clauses, unclear partici¬pation mechanisms and intermediary agency pressure tend to force PES on service-providers. Voluntary participation should be guaranteed by implementing organisations. In addition, PES policies should inte-grate peasants' perspectives (i. e. what do providers think they need?), so that PES is a tool for rather than a hurdle to rural development. PES schemes are introduced in contexts where natural resource distribution is skewed. PES could exacerbate this skewed distribution or even reduce the degree of control that the less powerful have over natural resources. In many situations, PES may result in service-providers not actually having access to the services they are helping to conserve, or losing control over their resources. PES should be tied to the fair redistribution of natural resource rights. PES may compete with communal organisations, and erode cultural and conservation practices that are not based on monetary payments.
Keywords: 330; Umwelt; Ökosysteme und Ressourcen